A Spatial Study of Waisai Central Business District, in response to Raja Ampat’s tourism potential, West Papua - Satriya Wahyu Firmandhani; I. Indriastjario; Retno Susanti; Humaira M. Rahmi (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2019)
This study aims to analyze the Waisai district in terms of spatial aspects, as an attempt to respond to tourism potential in Raja Ampat with descriptive qualitative methods using a built and architectural environment design approach responding to natural potential. The study successfully concluded that the Waisai District lacked tourism magnets that could attract tourists and support the Raja Ampat tourism sector, and recommended the revitalization of the tourism potential of Waisai city, such as beaches, pedestrian ways, and city parks, hence Raja Ampat can be known for not only its magnificent sea, but also the Waisai’s central business district (CBD).